ANALISA KUALITATIF DAN KUANTITATIF KANDUNGAN ALKOHOL PADA TAPAI KETAN DI KOTA BATUSANGKAR - Sari, Maya; Fajar, Najmiatul (Sainstek : Jurnal Sains dan Teknologi, 2018)
The black sticky tapai/ Tapai ketan hitam in Batusangkar, made by fermentating black sticky rice and yeast. The fermentation of black sticky tapai take several days to produce a sweet taste. This process may some assumption that the sweetness in black sticky tapai comes from alcohol as a result of sticky rice fermentation reaction with yeast. As the time of fermentation increases alcohol content, this raises doubt the halalness of black sticky tapai, because based on MUI Fatwa Number.4 in 2003 says the drinks containing ethanol (C2H5OH) more than one persen are categorized haram. Because of that, need some research to see the impact of duration fermentation to alcohol concentration on black sticky tapai in Batusangkar city. The reaserch data was obtained by distillation from various duration of fermentation. The result data were analyzed by product moment correlation test (? = 5%). Base on the research conducted, obtained information that in black sticky tapai contain etanol which has increased alcohol concentration along with the increase of fermentation duration. However, it becomes contradictory with the result of analysis where Y = 3,635 - 15,54 X, t arithmetic ? t table, that is 0,16 ? 3,18. This conclusions that there is no relationship between duration of fermentation with alcohol concentration.